IMPLEMENTASI PENDIDIKAN BAGI SISWA TUNANETRA DI SEKOLAH DASAR INKLUSI - Iwan Kurniawan (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
Inclusive education is an education which entered students with a special necessary to interact with another normal students. Inclusive education is about similarity of students human right. Inclusive education is a process to omit the backstop in order that the inclusive students can learn and work cooperatively with another normal students in their school. The terminology of inclusi or inclusive students, start put to the front since 1990, when the world conference about education for all, then continued with salamancaâ€™s statement about inclusive education in 1994. The concept of inclusive education was for to give a solution, because of there was a diskriminatif action at education service, especially to children special needed. Islam also teaches that all people are entitled to education and teaching regardlessbof rank, class, disability someone or something else. Islam strictly prohibits discrimination in education.Â Key Words: Education, Inclusive, Islam